The Influence of Green Human Resource Management Implementation on Organizational Citizenship Behavior for the Environment Mediated by Enablers of Green Organizational Culture in Private Banks Region 1 - Sandy Hani Eka Putra (Dinasti Publisher, 2025)
This study aims to analyze the influence of the role of Green Human Resource Management (GHRM) on Organizational Culture Towards Green Behavior Environment (OCBE), mediated by Enablers of Green Organizational Culture (GOC) in Regional 1 Private Bank. This research uses a quantitative method. The population in this study consists of all employees at PT. Regional 1 Private Bank, totaling 450 people. The sample size is determined by using the Slovin formula with a margin of error of 5% and a confidence level of 95%, resulting in 212 employees as research respondents. The sampling technique employed is purposive sampling, and the data is collected through an online questionnaire. The analysis method employed is the Structural Equation Modeling (SEM). The study's results indicate that Green Human Resource Management has a direct effect on Enables of Green Organizational Culture (Leadership Emphasis, Message Credibility, Peer Involvement, Employee Empowerment) and Organizational Citizenship Behavior Towards The Environment. Enables of Green Organizational Culture (Leadership Emphasis, Message Credibility, Peer Involvement, Employee Empowerment) have a direct effect on Organizational Citizenship Behavior Towards The Environment. Enables of Green Organizational Culture (Leadership Emphasis, Message Credibility, Peer Involvement, Employee Empowerment) positively mediate the relationship between Green Human Resource Management and Organizational Culture Towards Green Behavior Environment at Regional Private Bank 1.